Media Narratives and the COVID-19 Pandemic The Asian Experience (Taylor & Francis, 2024)
This volume investigates mediated lives and media narratives during the Covid-19 pandemic, with Asia as a focus point. It shows how the pandemic has created an unprecedented situation in this globalized world marked by many disruptions in the social, economic, political, and cultural lives of individuals and communities- creating a 'new normal'. It explores the different media vocabularies of fear, panic, social distancing, and contagion from across Asian nations. It focuses on the role media played as most nations faced lockdowns and unique challenges during the crisis. From healthcare workers to sex workers, from racism to nationalism, from the plight of migrant workers in news reporting to state propaganda, this book brings critical questions confronting media professionals into focus. The volume is of critical interest to scholars and researchers of media and communication studies, politics, especially political communication, social and public policy, and Asian studies.
English
Keywords: Media studies; Political structure & processes; Regional studies; Society & culture: general; media narratives,Marginalized Narratives,SARS,Gender, Media and the COVID-19 Pandemic,Risk Communication,COVID Pandemic,Pandemic Politics,Follow,Held,Clip,CCP,Tablighi Jamaat,UN,Pandemic Management,Vice Versa,Female Healthcare Workers,Media Narratives,Subcontinent,USA,SARS Epidemic,Yellow Peril,Chinese Government,Middle East Respiratory Syndrome Coronavirus,Star Online,Hindustan Times,Transgender Community Members,Corona Virus,CoV,Model Minority State,Lakshman Rekha,Violating,Weibo